Non‐Solvating and Low‐Dielectricity Cosolvent for Anion‐Derived Solid Electrolyte Interphases in Lithium Metal Batteries - Ding, Jun‐Fan; Xu, Rui; Yao, Nan; Chen, Xiang; Xiao, Ye; Yao, Yu‐Xing; Yan, Chong; Xie, Jin; Huang, Jia‐Qi (Angewandte Chemie International Edition, 2021)
Lithium (Li) metal anodes hold great promise for next‐generation high‐energy‐density batteries, while the insufficient fundamental understanding of the complex solid electrolyte interphase (SEI) is the major obstacle for the full demonstration of their potential in working batteries. The characteristics of SEI highly depend on the inner solvation structure of lithium ions (Li+). Herein, we clarify the critical significance of cosolvent properties on both Li+ solvation structure and the SEI formation on working Li metal anodes. Non‐solvating and low‐dielectricity (NL) cosolvents intrinsically enhance the interaction between anion and Li+ by affording a low dielectric environment. The abundant positively charged anion–cation aggregates generated as the introduction of NL cosolvents are preferentially brought to the negatively charged Li anode surface, inducing an anion‐derived inorganic‐rich SEI. A solvent diagram is further built to illustrate that a solvent with both proper relative binding energy toward Li+ and dielectric constant is suitable as NL cosolvent. The introduction of cosolvents with non‐solvating and low‐dielectricity (NL) properties can intrinsically enhance the interaction between anion and Li+ and regulate the solvation structures in electrolytes, which favors an upgraded anion‐derived solid electrolyte interphase (SEI) on lithium metal anodes.